Mulla Sadra's Philosophical Concept - Ahmad Hisyam Syamil; Muhammad Kholid Muslih; Amir Reza Kusuma (al-Afkar, Journal For Islamic Studies, 2025)
Mulla Sadra named Islamic philosophy as al-Hikmah al-Muta'aliyah. According to him, al-hikmah al-muta'aliyah is knowledge based on intellectual intuition (irfan or isyraqi dzawq), rational proof ('aql or istidlal), and sharia (burhani). Al-Hikmah al-Muta'aliyyah is a synthesis of three styles of thought, namely: theology with a dialectical, polemical pattern (jaddaly), philosophy with a demonstrative pattern (burhany), and theosophy with an illuminationist and gnostic pattern (dzawq). This research uses descriptive analysis methods to explore Mulla Sadra's philosophical thinking. The results of this research reveal that the building of thought that was successfully built by Mulla Sadra through his synthesis of thought had a major influence on the development of philosophy in Persia, India and Iraq. However, the interesting thing is that Sadra brought him into contact with the truth of the Koran and Hadith. The harmonization he carried out resulted in a synthesis, namely integrating it through the three paths of Al-Qur'an (revelation), Burhan (demonstration or intellect), Irfan (spiritual or mystical). Because the three of them are not contradictory in their aim of achieving truth. The depiction of Mulla Sadra's philosophy can be done well by referring to his Ontology, Theology, Physics and Eschatology.